Probing Stress States in Silicon Nanowires During Electrochemical Lithiation Using In Situ Synchrotron X-Ray Microdiffraction - Ali, Imran; Tippabhotla, Sasi Kumar; Radchenko, Ihor; Al-Obeidi, Ahmed; Stan, Camelia V.; Tamura, Nobumichi; Budiman, Arief Suriadi (Frontiers in Energy Research, 2018)
Silicon is considered as a promising anode material for the next generation lithium-ion battery due to its high capacity at nanoscale. However, silicon expands up to 300% during lithiation, which induces high stresses and leads to fractures. To design silicon nanostructures that could minimize fracture, it is important to understand and characterize stress states in the silicon nanostructures during lithiation. Synchrotron X-ray microdiffraction has proven to be effective in revealing insights of mechanical stress and other mechanics considerations in small-scale crystalline structures used in many important technological applications, such as microelectronics, nanotechnology and energy systems. In the present study, an in situ synchrotron X-ray microdiffraction experiment was conducted to elucidate the mechanical stress states during the first electrochemical cycle of lithiation in single-crystalline silicon nanowires (SiNWs) in a lithium-ion battery test cell. Morphological changes in the SiNWs at different levels of lithiation were also studied using scanning electron microscope (SEM). It was found from SEM observation, that lithiation commenced predominantly at the top-surface of SiNWs followed by further progression towards the bottom of the SiNWs gradually. The hydrostatic stress of the crystalline core of the SiNWs at different levels of electrochemical lithiation was determined using the in situ synchrotron X-ray microdiffraction technique. We found that the crystalline core of the SiNWs became highly compressive (up to - 325.5 MPa) once lithiation started. This finding helps unravel insights about mechanical stress states in the SiNWs during the electrochemical lithiation, which could potentially pave the path towards the fracture-free design of silicon nanostructure anode materials in the next generation lithium-ion battery.